2003
DOI: 10.1128/jvi.77.22.12152-12164.2003
|View full text |Cite
|
Sign up to set email alerts
|

Human T-Cell Leukemia Virus Type 1 Tax Oncoprotein Suppression of Multilineage Hematopoiesis of CD34+Cells In Vitro

Abstract: Human T-cell leukemia virus type 1 (HTLV-1) and HTLV-2 are highly related viruses that differ in disease manifestation. HTLV-1 is the etiologic agent of adult T-cell leukemia and lymphoma, an aggressive clonal malignancy of human CD4-bearing T lymphocytes. Infection with HTLV-2 has not been conclusively linked to lymphoproliferative disorders. We previously showed that human hematopoietic progenitor (CD34 ؉ ) cells can be infected by HTLV-1 and that proviral sequences were maintained after differentiation of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
53
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(57 citation statements)
references
References 106 publications
4
53
0
Order By: Relevance
“…Collectively, the phenotypes displayed by Tax-2 in these models are consistent with Tax-2 retaining a less robust transformation potential in comparison to Tax-1. Furthermore, the ability of Tax-1 to induce G 0 /G 1 cell cycle arrest in HPCs and suppress hematopoiesis, in distinct contrast to Tax-2, allows speculation that the fate of infected HPCs following HTLV-1 and HTLV-2 infection may be fundamentally different in vivo (Tripp et al, 2003;Feuer, unpublished observations).…”
Section: Distinct Tax-1 and Tax-2 Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Collectively, the phenotypes displayed by Tax-2 in these models are consistent with Tax-2 retaining a less robust transformation potential in comparison to Tax-1. Furthermore, the ability of Tax-1 to induce G 0 /G 1 cell cycle arrest in HPCs and suppress hematopoiesis, in distinct contrast to Tax-2, allows speculation that the fate of infected HPCs following HTLV-1 and HTLV-2 infection may be fundamentally different in vivo (Tripp et al, 2003;Feuer, unpublished observations).…”
Section: Distinct Tax-1 and Tax-2 Activitiesmentioning
confidence: 99%
“…Lentivirus-mediated transduction of Tax-1 in HPCs suppressed hematopoiesis in vitro and led to increased cell cycle arrest in G 0 /G 1 . Tax-1 transduced HPCs displayed concomitant activation of endogenous p21 cip1/waf1 and p27 kip1 expression (Tripp et al, 2003) (Tripp and Feuer, unpublished observations). Interestingly, Tax-2 failed to arrest HPCs in G 0 /G 1 , failed to suppress hematopoiesis and did not detectably modulate endogenous p21 cip1/waf1 and p27 kip1 gene expression.…”
Section: Role Of Nfjb and Creb/atf In Htlv Tax-mediated Transformationmentioning
confidence: 99%
“…ϩ hematopoietic progenitor cells in comparison to Tax2 (11,34,50,60,61). Tax1 and Tax2 also demonstrate unique patterns of subcellular localization in lymphoid cells (35).…”
mentioning
confidence: 99%
“…It was also demonstrated that reconstitution of T lymphopoiesis with HTLV-1-infected CD34 ϩ cells in severe combined immunodeficient mice engrafted with human thymus and liver tissues (SCID-hu) resulted in the perturbation of thymopoiesis and an aberrant display of thymocyte subpopulations (13). Furthermore, it has been shown that HTLV-1 Tax-transduced hematopoietic (CD34 ϩ ) cells isolated from human fetal liver have a reduced capacity to proliferate, as evidenced by the induction of cell cycle arrest and the concomitant suppression of multilineage hematopoiesis (41,42).…”
mentioning
confidence: 99%